Substituição parcial do farelo de soja por outras fontes proteicas sobre a ingestão, digestibilidade, utilização do nitrogênio, eficiência de utilização dos grãos e comportamento de bovinos de corte Bos indicus alimentados com dietas de milho grão inteiro - Sousa, Reginaldo Martins de (2021)
The experiment was conducted to assess the effects of replacement of 50% of soybean meal with other protein sources on intake, digestibility, nitrogen utilization, efficiency grain use, metabolic parameters and diurnal behavior of cattle fed whole corn grain diets, without roughage inclusion. Were used five Nelore cattle uncastrated (BW 651.6 ± 31.83 kg) rumen cannulated distributed in 5 x 5 Latin square design. Treatments: SM – 85% of whole corn grain with 15% of a pelleted supplement with soybean meal; CM – 85% of whole corn grain with 15% of a pelleted supplement cottonseed with meal plus soybean meal; SFM – 85% of whole corn grain with 15% of a pelleted supplement with sunflower meal plus soybean meal; DDG – 85% of whole corn grain with 15% of a pelleted supplement with Distillers Dried Grains plus soybean meal; DDGS – 85% of a whole corn grain with 15% of pelleted supplement with Distillers Dried Grains with Soluble plus soybean meal. The dry matter intake (DMI kg / d and% BW) and organic matter (OMI) were higher (P <0.05) in DDG treatment. There was a tendency (P = 0.066) of higher intake of CP with DDG compared to CM and intermediate for SM, SFM and DDGS. The digestibility of diets and nutrients were not affected (P> 0.05) by protein sources. The efficiency grain use were not affect (P> 0.05) by protein source. Of 30914 whole corn grains daily intake, 3.38% were recovered in feces, obtaining 96.62% of efficiency grain use. There was a tendency (P = 0.066) of higher N intake with DDG inclusion and no effect (P> 0.05) of the protein source on the N use efficiency. The diurnal behavior of the cattle was similar (P> 0.05) between treatments. The time spent eating at feed bunk, ingesting water and ruminating was 96 min, 8.5 min and 15 min, respectively. The replacement of 50% of soybean meal by other protein sources in whole corn grain diets did not affect the evaluated parameters.